Endophytic Microbial Consortia of Phytohormones-Producing Fungus Paecilomyces formosus LHL10 and Bacteria Sphingomonas sp. LK11 to Glycine max L. Regulates Physio-hormonal Changes to Attenuate Aluminum and Zinc Stresses - Bilal, Saqib; Shahzad, Raheem; Khan, Abdul L.; Kang, Sang-Mo; Imran, Qari M.; Al-Harrasi, Ahmed; Yun, Byung-Wook; Lee, In-Jung (Frontiers in Plant Science, 2018)
The compatible microbial consortia containing fungal and bacterial symbionts acting synergistically are applied to improve plant growth and eco-physiological responses in extreme crop growth conditions. However, the interactive effects of phytohormones-producing endophytic fungal and bacterial symbionts plant growth and stress tolerance under heavy metal stress have been least known. In the current study, the phytohormones-producing endophytic Paecilomyces formosus LHL10 and Sphingomonas sp. LK11 revealed potent growth and tolerance during their initial screening against combined Al and Zn (2.5 mM each) stress. This was followed with their co-inoculation in the Al- and Zn-stressed Glycine max L. plants, showing significantly higher plant growth attributes (shoot/root length, fresh/dry weight, and chlorophyll content) than the plants solely inoculated with LHL10 or LK11 and the non-inoculated (control) plants under metal stresses. Interestingly, under metal stress, the consortia exhibited lower metal uptake and inhibited metal transport in roots. Metal-induced oxidative stresses were modulated in co-inoculated plants through reduced hydrogen peroxide, lipid peroxidation, and antioxidant enzymes (catalase and superoxide dismutase) in comparison to the non-inoculated plants. In addition, endophytic co-inoculation enhanced plant macronutrient uptake (P, K, S, and N) and modulated soil enzymatic activities under stress conditions. It significantly downregulated the expression of heavy metal ATPase genes GmHMA13, GmHMA18, GmHMA19, and GmPHA1 and upregulated the expression of an ariadne-like ubiquitin ligase gene GmARI1 under heavy metals stress. Furthermore, the endogenous phytohormonal contents of co-inoculated plants revealed significantly enhanced gibberellins and reduced abscisic acid and jasmonic acid contents, suggesting that this endophytic interaction mitigated the adverse effect of metal stresses in host plants. In conclusion, the co-inoculation of the endophytic fungus LHL10 and bacteria LK11 actively contributed to the tripartite mutualistic symbiosis in G. max under heavy metal stresses; this could be used an excellent strategy for sustainable agriculture in the heavy metal-contaminated fields.